Path Planning System for Smart Cars Used in Education - Xiong, Guangyu; Niu, Lulu; Tian, Yanfu; Zhou, Jiehan; Mohajeri, Babak; Nyberg, Timo R. (2020 15th IEEE Conference on Industrial Electronics and Applications (ICIEA), 2020)
In this paper, we developed a path planning system for smart cars for teaching electronic engineering or computer science, which consists of the interactive platform for smart cars development and path planning. Designed by Visual C++, the interactive platform can call Matlab engine, allows users to choose path optimization algorithms such as genetic or A-star(A*) algorithm for different tasks and control smart cars through serial ports. The simulation and practice demonstrate that our interactive platform can help learners to plan paths and control intelligent vehicles without specially designing a user interface.